Relationship between the numerical condition and court position in goal scoring in women`s handball - Cherobini Piovesan, C.; Geremia, J. M.; Luz, C.; Pombo Menezes, R.; Saraiva Flores, F. (Journal of Physical Education and Sport, 2020)
Introduction: Handball is characterized by the constant action of attacking and defending, using a common space in the court. In this highly dynamic sport, one of the main factors that affect performance is the numerical condition. Despite its importance, studies concerning female handball lacks investigations regarding the numerical condition and the court position during attacks. Thus, the present study aimed to analyze the relationship between the numerical condition and the court position during the shoots in female handball world championships. Materials and Methods: The analysis was performed using indirect observation of the match recordings. Twenty-five matches of the three last championship teams of the handball world championships were observed, and information regarding the numerical conditions (inferiority, superiority, and equality), and court positions during the attacks were collected. Results: The results showed that most of the shots were goals scored (57.6%), and most of the goals occur in numerical equality (80.6%). Brazil scored 55.2% (264 goals) of the occasions. France scored in 59.6% (238 goals), and Norway scored in 58.7% (193 goals). Also, there are differences between the numerical condition and the distance to the goalpost concerning the goals scored, but no differences were found between the numerical condition and the regions of the court, or goals scored and numerical condition of each team. Conclusions: The findings demonstrate that the numerical condition and the court position during female handball games can influence the shoots, being important variables to coaches and team preparation, which need to be taking to account during the season.Understanding this relationship can also be imperative for the organization of training and game planning. The studied variables show the main idea of the champion team`s game model, being important to understand goals and winners in handball matches.